Age-Related Differences in Strategy in the Hand Mental Rotation Task - Nagashima, Izumi; Takeda, Kotaro; Harada, Yusuke; Mochizuki, Hideki; Shimoda, Nobuaki (Frontiers in Human Neuroscience, 2021)
Individuals seem to use one of two strategies to perform the hand mental rotation task (HMRT), which involves observing a picture of a hand and determining whether it depicts a left or right hand. One is the motor imagery (MI), which involves simulating one’s own hand movements. This involves the medial-lateral effect, wherein the response time varies according to the difficulty of performing the actual motion. The other is the visual imagery (VI), which involves mentally rotating the picture of the hand; this strategy does not involve the medial-lateral effect. These strategies must be investigated further as the rehabilitative benefits of the HMRT are thought to involve the MI strategy. Subjects of different ages were included in the present study as the strategy adopted to perform the HMRT might differ based on age, type of image presented (palm or back of hand), and performance. When presented with pictures of the palm, subjects performed the HMRT via the MI strategy, regardless of age and performance. In contrast, when subjects were presented with pictures of the back of the hand, the VI strategy predominated among the young age group regardless of their performance, while those in the middle-age and elderly groups used different strategies depending on their performance. In the elderly group, the VI approach predominated in those with high performance skill, whereas the MI strategy predominated among those with low performance skill. This MI-based study showed that middle-aged and elderly individuals may not necessarily form a motion image in the HMRT.